2008
DOI: 10.1186/1471-2199-9-71
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of Caenorhabditis elegans noncoding RNA promoter motifs

Abstract: Background: Noncoding RNAs (ncRNAs) play important roles in a variety of cellular processes. Characterizing the transcriptional activity of ncRNA promoters is therefore a critical step toward understanding the complex cellular roles of ncRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…The most striking feature of the data was the unexpected appearance of strong RNA signals mapping upstream of the annotated transcription start site (aTSS) of 51 snoRNA genes upon NPP-13 knockdown (Figure 1C, D & Figure S1A). Previous studies had proposed that the C. elegans snoRNAs transcribed by RNA Pol III are generated by cleavage of larger precursor RNAs originating upstream of the aTSS (Li et al, 2008; Xiao et al, 2012) (Figure 1E). We performed Northern Blotting to test if aberrant accumulation of these predicted precursor snoRNAs might account for the upstream RNA-seq signals.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking feature of the data was the unexpected appearance of strong RNA signals mapping upstream of the annotated transcription start site (aTSS) of 51 snoRNA genes upon NPP-13 knockdown (Figure 1C, D & Figure S1A). Previous studies had proposed that the C. elegans snoRNAs transcribed by RNA Pol III are generated by cleavage of larger precursor RNAs originating upstream of the aTSS (Li et al, 2008; Xiao et al, 2012) (Figure 1E). We performed Northern Blotting to test if aberrant accumulation of these predicted precursor snoRNAs might account for the upstream RNA-seq signals.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of closely located terminators, resulting in the incorporation of long 3′ trailers into pre-tRNAs, might be more widespread than expected in eukaryotes. Known examples of this ncRNA expression strategy are, for example, the dicistronic tRNA transcription units in yeast (Willis et al, 1984) and Trypanosoma brucei (LeBlanc et al, 1999), the tRNA-snoRNA dicistronic units in plants (Kruszka et al, 2003) and Caenorhabditis elegans (Li et al, 2008), the dicistronic tRNA-5S rRNA genes in Yarrowia lipolytica (Acker et al, 2008), the composite tRNA-like-miRNA transcription units in murine gammaherpesvirus 68 genome (Pfeffer et al, 2005), the polycistronic tRNA transcription units in Chlamydomonas reinhardtii, whose genome also contains individual tRNA genes lacking a terminator close to the tRNA 3′ end (Cognat et al, 2008). It can thus be anticipated that more thorough analyses of Pol III transcription units in the ever increasing number of complete genome sequences will reveal more cases of functional ncRNAs synthesized as 3′ trailers of tRNAs or other Pol III transcripts, and, at the same time, more examples of non-canonical termination signals, whose existence has been sparsely documented in the past (Emerson and Roeder, 1984;Hess et al, 1985).…”
Section: Pol III Termination Signals: Strengths and Weaknesses Of T-rmentioning
confidence: 99%
“…1B,C). The 5.8S rRNA was significantly depleted in the TEX-treated library (0.3% of all reads) compared to the control library (11% of all reads), whereas snRNAs and stem-bulge RNAs (sbRNAs), known to be primary RNA pol II transcripts bearing 59-terminal cap or pol III transcripts with tri-phosphate 59-terminal structures (Deng et al 2006;Li et al 2008), were strongly enriched in the TEX-treated library (Supplemental Fig. S3A).…”
Section: Sequencing and Data Analysismentioning
confidence: 99%
“…S3B). UM2 snoRNAs are probably processed from longer primary transcripts encompassing the UM2 sequence (Li et al 2008), which is likely to generate mature snoRNAs with 59 monophosphate termini. The sequencing data indicated that ''UM2-snoRNA'' primary transcripts could be detected for 16 of the 48 UM2 snoRNAs (Fig.…”
Section: Analysis Of Snornas Suggests Secondary 59-end Modificationmentioning
confidence: 99%